Mutagenic and antimutagenic properties of some lichen species grown in the eastern Anatolia region of Turkey - Aslan, A.; Gulluce M.; Agar G.; Karadayi M.; Bozari S.; Orhan F. (My University, 2012)
All the methanol extracts did not show mutagenic activity in Ames/Salmonella and Z. mays MI test systems. Furthermore, some extracts showed significant antimutagenic activity against 9-AA in Ames test system. Inhibition rates for 9-AA mutagenicity ranged from 25.51% (P. furfuracea-0.05 ?g/plate) to 66.14% (C. islandica-0.05 ?g/plate). In addition, all of the extracts showed significant antimutagenic activity against sodium azide (NaN3) mutagenicity on MI values of Z. mays. © 2012 Allerton Press, Inc.